Pengaruh Sistem Pengendalian Internal, Pemanfaatan Teknologi Informasi terhadap Kualitas Laporan Keuangan dengan Kompetensi Sumber Daya Manusia sebagai Variabel Mediasi - Sukmawati Melati Putri Kedaton; Suwandi Suwandi (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2026)
The study aims to analyze the influence of internal control systems and the use of information technology on the quality of financial reports, with human resource competence serving as a mediating variable. The study was conducted at 18 Community Health Centers (Puskesmas) in Gresik Regency, with the main indicators being internal control systems, the use of information technology, financial report quality, and human resource competence. Using purposive sampling, a sample of 70 respondents comprising the population of Puskesmas employees in the Gresik region was selected for the study. The Partial Least Squares Structural Equation Modeling (SEM-PLS) method was used as the data analysis technique after all primary data were collected via a questionnaire specifically designed to represent the relevant variables. Based on the research results, the quality of financial reports has a positive impact when utilizing an information technology-based internal control system. However, human resource competence does not have a maximal impact on the utilization of the internal control system; nevertheless, a positive impact can be leveraged through the use of information technology. Further mediation analysis indicates that human resource competency mediates the correlation between internal control systems and financial statement quality. Conversely, human resource competency does not mediate the relationship between the utilization of information technology and financial statement quality. This study underscores the importance of internal control systems, the utilization of information technology, and human resource competency in producing optimal financial statement quality.